Managerial competencies: comparing conventional and Islamic perspectives - Nik Mutasim Nik Ab. Rahman,; Nur Atiqah Abdullah,; Khairul Akmaliah Adham,; Norazila Mat, (Penerbit Universiti Kebangsaan Malaysia, 2014)
The objective of this article is to share the authors’ understanding of the concept of managerial or executive competencies from the Islamic perspective. The paper discusses managerial competencies models developed by Western researchers and compares them with the Islamic models. The striking differences between the two approaches are in each model’s philosophy and stance. The Islamic model holds firmly to the divine principles, which serve as a foundation for managers to achieve their worldly goals, without separating life in this world from life in the hereafter. On the contrary, conventional models are developed based on culture and value of thought.